Detection of water-filled mining goaf using mining transient electromagnetic method - Chang, Jianghao (IEEE Xplore, 2020)
Water-filled mining goaves are extremely prone to water inrush accidents in coal mines, and the transient electromagnetic method (TEM) is a good geophysical method for detecting water-rich areas. Considering that conventional TEM was mainly carried out on the ground, to increase the detection resolution, the underground TEM was used to detect the water-filled goaves in this study. Based on the whole-space model, the data processing method of the underground TEM was studied. The whole-space geo-electric model was established based on actual coal-measure strata data, and the whole-space TEM response of the water-filled goaves was modeled using the finite-difference time-domain method. The results showed that the low-resistance areas of the apparent resistivity contours can accurately reflect the water abundance of the mining goaves. The underground TEM was used to detect the water abundance of the mining goaf in a mine environment and its detection results were consistent with the actual results.